2021
DOI: 10.1186/s40168-021-01052-7
|View full text |Cite
|
Sign up to set email alerts
|

Iron status influences non-alcoholic fatty liver disease in obesity through the gut microbiome

Abstract: Background The gut microbiome and iron status are known to play a role in the pathophysiology of non-alcoholic fatty liver disease (NAFLD), although their complex interaction remains unclear. Results Here, we applied an integrative systems medicine approach (faecal metagenomics, plasma and urine metabolomics, hepatic transcriptomics) in 2 well-characterised human cohorts of subjects with obesity (discovery n = 49 and validation n = 628) and an inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 45 publications
1
63
1
1
Order By: Relevance
“…Metabolomics and transcriptomics are two methods of profiling that have been frequently used to provide information regarding pathological phenotypes 8 or for the aim of pathogenesis studies 9 , drug-target identification 10 , and biomarker recognition 11 etc. Liquid chromatography–mass spectrometry (LC–MS), as a robust and informative tool in identifying and quantifying molecules in mixtures, could be used to get reliable data regarding the metabolites in tissues, making metabolic comparison between phenotypes possible.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics and transcriptomics are two methods of profiling that have been frequently used to provide information regarding pathological phenotypes 8 or for the aim of pathogenesis studies 9 , drug-target identification 10 , and biomarker recognition 11 etc. Liquid chromatography–mass spectrometry (LC–MS), as a robust and informative tool in identifying and quantifying molecules in mixtures, could be used to get reliable data regarding the metabolites in tissues, making metabolic comparison between phenotypes possible.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic steatosis has a risk of steatohepatitis, fibrosis, cirrhosis, liver failure, and HCC, and it was reported that dysregulation of microbial metabolites such as aromatic and branched-chain amino acid (AAA and BCAA) or of iron metabolism are related to liver fat accumulation and facilitate steatosis [ 46 , 47 ]; however, additional factors, such as insulin resistance, oxidative stress, ER stress, and mitochondrial dysfunction, are also involved in a disease progression [ 37 , 38 ]. Because the sequential esterification of fatty acids into a glycerol backbone to generate TG and budding as nascent LDs occur at the ER membrane, LDs are closely associated with ER homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of metabolomics and lipidomics, alongside integration with transcriptomics data, has prompted identification of targets to further explore for treatment in, or prevention of, human NAFLD [ [40] , [41] , [42] , [43] ]. A two-stage metabolic and molecular screening of liver tissue showed that hydroquinone and nicotinic acid were inversely correlated with histological NAFLD severity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%